Traffic Analysis for Ramp Junction on Freeway and City Entrance- Case study: Jabla& Qerdaha Junction- - رستم , أكرم; لولو, عبير (Latakia University Journal -Engineering Sciences Series, 2020)
The Revelation of Technology tools help the innovation of traffic analysis tools. These tools are divert. One of the most common code in traffic field is HCM. It uses in operational analyze, planning and designing. In this study, we focus on the operational analyses of Ramps using Hcm2000 and Hcs2000. Areas of study are Jabla& Qerdaha junctions. The evaluation of these junctions depend on LOS; the LOS A=are A for all Ramps .While the FFS are 90 km/h for the freeway and 60 km/h for the Ramps, the Calculate speed are 55 Km/h for Ramps& 87km/h for the freeway.